DIVERSIFICATION OF STUDENTS' SCIENTIFIC CREATIVITY IN A VIRTUAL ENVIRONMENT - Vera S. Fedotova (Высшее образование в России)
The purpose of the study is to identify strategic forms of organization of students' scientific work in a virtual environment. The study methods were the analysis of information about the advantages and disadvantages of Internet services and technologies and the generalized ICT practices in the organization of students' research work. The main results consist in positioning scientific creativity of students as a socially important component of professional training at University that promotes personal and professional development of students. The author proves the relevance of the organization of students' scientific work using the powerful potential of modern ICT and Internet technologies in conditions of general informatization of education. The paper shows the possibility of diversification of research activities of students in online space by means of Internet technologies using the potential of scientific social networking, blogs, forums, online conferences, online seminars, webinars, chat, email, multimedia technologies, direct contact technology, electronic and hybrid journals, institutional repositories, electronic preprints, personal pages, scientometric databases, electronic library catalogs, scientific electronic library. All these instruments can be effectively used in working with students.